An examination of job engagement, transformational leadership, and related psychological constructs - Wefald, Andrew J. (Kansas State University, 2008)
Job engagement is an emerging psychological construct that purports to measure individuals' level of psychological presence at work. The concept has received attention in both the academic literature and in industry. In the academic literature three measures of engagement exist that were examined in this research (Schaufeli, Britt, & Shirom). However, engagement has undergone little critical examination beyond factor analyses. This research sought to critically examine the concept of engagement as well as provide empirical evidence regarding its place in the nomological network of job attitudes. Both theoretically and empirically, engagement has been linked to personality and leadership variables; however, no research to date has attempted to examine all three concepts together. This research additionally sought to link engagement, personality, and leadership in a theoretically based model. Participants (N=382) at mid-sized financial institution completed a survey comprised of demographic items, attitude measures, a leadership measure, and a personality measure. Results indicated that the Schaufeli and Britt measures of engagement substantially overlap with job satisfaction and affective commitment; however, the Shirom measure (called vigor) is not redundant with job satisfaction or affective commitment. Hypothetical models of engagement, personality, and leadership were not good fits with the data; however, two modified models (one with Schaufeli's engagement and one with Shirom's vigor) had marginally acceptable fits. Further, hierarchical regressions indicated a strong connection between engagement and leadership and between engagement and personality. It seems that every so often a "new" concept comes along that offers organizations prosperity with little cost. Engagement is a popular and positive concept that is appealing to both practitioners and academics. Engagement, as a construct, is not a silver bullet for organizations. However, engagement or vigor may be a useful concept for organizations as both a selection instrument and as a way to assess the relative states of fulfillment of employees, groups, and organizations. Future directions for research and recommendations are discussed.
Keywords: Engagement; Leadership; Personality; Job attitudes; Vigor; Psychology, Industrial (0624)